PHYSICAL ACTIVITY AND CARDIOVASCULAR AGING: THE MECHANISM AND RECENT EVIDENCES - Handayani, Theressia; Lawrence, Cynthia; Tanjung, Ni Luh Okta Saktiadewi; Prabowo, Angelia Ongko; Wijayanti, Stephanie; Dewi, Luh Putu Liana Indayana; Daniati, Dana; Dewi, Luh Gede Wiwin Witsari; Juhanna, Indira Vidiari (Sport and Fitness Journal, 2021)
ABSTRACT Successful aging in population means preserving life quality and reducing the health burden. Many factors influence the  successful aging, including physiological, psychological, social, and lifestyle factors.  Physical activity is an important lifestyle factor that can prevent the  chronic diseases, increase longevity and survival, and also improve cognitive and physical functions in elderly. The aim of this narrative review is to explain the correlation between physical activity and successful aging. Recent systematic review showed the benefit of exercise for overall health and cardiovascular system. Physical activity promotes successful aging among middle-aged and older adults especially in the younger population.   Keywords : exercise; healthy life style; cardic aging